The Political Economy of Regulatory Risk - Roland Strausz (Verein für Socialpolitik, 2010)
The paper investigates political uncertainty as a source of regulatory risk. It shows that political parties have incentives to reduce regulatory risk actively: Mutually beneficial pre-electoral agreements that reduce regulatory risk always exist and fully eliminate it when political divergence is small or electoral uncertainty is appropriately skewed. These results follow from a fluctuation effect of regulatory risk that hurts both parties and an output-expansion effect that benefits at most one party. Due to commitment problems, politically independent regulatory agencies are needed to implement pre-electoral agreements. Optimal delegation may require only partial rather than full political independence.
Keywords: D82; L51; L12; 330; regulation; regulatory risk; political economy; electoral uncertainty; independent regulatory agency